2017
DOI: 10.1002/pd.5140
|View full text |Cite
|
Sign up to set email alerts
|

Fetal isovolumetric time intervals as a marker of abnormal cardiac function in fetal anemia from homozygous alpha thalassemia‐1 disease

Abstract: Isovolumetric contraction time was significantly prolonged in fetal anemia from homozygous alpha thalassemia-1 during the early stage of hydropic changes. Because of its simple measurement and high efficacy, ICT can be a useful marker for prenatal screening of abnormal cardiac function in fetal anemia. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This finding indicated that foetuses with anaemia have subtle changes in myocardial function from late first trimester, and the earliest sign is prolonged ICT. Similarly, Tongprasert et al 47 . demonstrated that among foetuses with Hb Bart's disease at mid‐pregnancy (18–22 weeks), ICT was significantly longer compared with unaffected foetuses.…”
Section: Haemodynamic Changes In Foetal Haemoglobin Bart's Diseasementioning
confidence: 89%
See 1 more Smart Citation
“…This finding indicated that foetuses with anaemia have subtle changes in myocardial function from late first trimester, and the earliest sign is prolonged ICT. Similarly, Tongprasert et al 47 . demonstrated that among foetuses with Hb Bart's disease at mid‐pregnancy (18–22 weeks), ICT was significantly longer compared with unaffected foetuses.…”
Section: Haemodynamic Changes In Foetal Haemoglobin Bart's Diseasementioning
confidence: 89%
“…Anaemic foetuses can perfectly maintain normal diastolic flow. Additionally, some studies on myocardial performance indicated that isovolumetric relaxation time is unchanged in foetal anaemia, 46,47 suggesting no significant impact on afterload in spite of increased blood volume.…”
Section: Functional Changesmentioning
confidence: 99%
“…Note that this finding is usually not seen in hydrops fetalis resulting from other anemic causes. In most cases, hydrops fetalis due to anemia secondary to any cause other than Hb Bart disease is associated with polyhydramnios, 52–55 resulting from hypervolemia with high renal blood flow, with no severe asphyxia leading to fetal oliguria.…”
Section: High‐output Hydropic Phasementioning
confidence: 99%
“…• Tongprasert et al 55 compared fetal cardiac function, represented by the Tei index, between 28 fetuses with Hb Bart disease and 42 unaffected fetuses at midpregnancy (18–22 weeks). They found that in the affected fetuses, the ICT and ICT + isovolumetric relaxation time were significantly longer than those of unaffected fetuses (47.9 ± 12.5 versus 35.0 ± 6.7 milliseconds; P < .001; and 96.2 ± 13.6 versus 80.9 ± 10.6 milliseconds; P < .001 respectively).…”
Section: Low‐output Hydropic Phasementioning
confidence: 99%
“…A modified index was recently proposed as (ICT + IRT)/VFT, which has been shown significantly decreasing with gestational age, while no significant correlation of MPI with gestational ages was found (Khandoker et al , 2016). From a clinical standpoint, PEP, ICT, IRT, VET are the most useful cardiac intervals for assessing fetal development and wellbeing, as sensitive markers of the functional state of the fetal myocardium, cardiac performance and ANS function, and can reflect the early development of hypoxemia and acidosis (Tongprasert et al , n.d.; Hassan et al , 2013; Velayo et al , 2011; Mensah-Brown et al , 2010; Cruz-Martínez et al , 2012; Yumoto et al , 2005; Marzbanrad et al , 2016).…”
Section: D-dus Applications For Fetal Monitoringmentioning
confidence: 99%